Optimal exercise protocol for osteogenic response - Umemura, Y. (The Journal of Physical Fitness and Sports Medicine, 2016)
The contractile function of skeletal muscles is comprised of 3 major elements: strength (maximum muscle strength), speed (contractile velocity), and fatigue resistance (endurance). In sport science, the muscle contractile function facilitating exercise is a notable muscle function, and many studies have investigated the, training effects on skeletal muscle. In the sport science field, various training effects on skeletal muscle have been examined. For example, the level of protein forming the muscular microstructure and composition of muscle fiber type change. Recently, in skeletal muscle training experiments, correlation between changes in molecular and gene control systems in response to training have been attracting attention; however, few studies have simultaneously measured the contractile properties. In this review, the experimental significance of measuring the muscle contractile function has been outlined with reference to previous studies.